2018
DOI: 10.1007/s10772-018-9502-0
|View full text |Cite
|
Sign up to set email alerts
|

Emirati-accented speaker identification in each of neutral and shouted talking environments

Abstract: This work is devoted to capturing Emirati-accented speech database (Arabic United Arab Emirates database) in each of neutral and shouted talking environments in order to study and enhance text-independent Emirati-accented "speaker identification performance in shouted environment" based on each of "First-Order Circular Suprasegmental Hidden Markov Models (CSPHMM1s), Second-Order Circular Suprasegmental Hidden Markov Models (CSPHMM2s), and Third-Order Circular Suprasegmental Hidden Markov Models (CSPHMM3s)" as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Mel Frequency Cepstral Coefficient (MFCC) is the most commonly used feature extraction techniques in speaker [25], [26] and emotion [27], [28] recognition. MFCC gives the logarithmic perception of onset and pitch of the human auditory system.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Mel Frequency Cepstral Coefficient (MFCC) is the most commonly used feature extraction techniques in speaker [25], [26] and emotion [27], [28] recognition. MFCC gives the logarithmic perception of onset and pitch of the human auditory system.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Shahin et al [30] proposed a novel classifier called the cascaded GMM deep neural network (GMM-DNN) to enhance text-independent SI performance using two corpora: the Emirati speech database and ''speech under simulated and actual stress'' English database. Additionally, Shahin et al [29] identified Emirati-accented speakers in neutral talking and shouting environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where i Ψ is the probability of a state si at time t = 1 and aijk is the probability of the transition from a state si to a state sk at time t = 3. Prob t t 1 t 2 t 3 t 3 3 2 1 1 1 (5) Supplementary information about HMM3s can be found in reference [14]".…”
Section: Third-order Hidden Markov Modelsmentioning
confidence: 99%